Metformin Reverses the Enhanced Myocardial SR/ER–Mitochondria Interaction and Impaired Complex I-Driven Respiration in Dystrophin-Deficient Mice - Angebault, Claire; Panel, Mathieu; Lacôte, Mathilde; Rieusset, Jennifer; Lacampagne, Alain; Fauconnier, Jérémy (Frontiers in Cell and Developmental Biology, 2021)
Besides skeletal muscles dysfunction, Duchenne muscular dystrophy (DMD) exhibits a progressive cardiomyopathy characterized by an impaired calcium (Ca2+) homeostasis and a mitochondrial dysfunction. Here we aimed to determine whether sarco-endoplasmic reticulum (SR/ER)-mitochondria interactions and mitochondrial function were impaired in dystrophic heart at the early stage of the pathology. For this purpose, ventricular cardiomyocytes and mitochondria were isolated from 3-month-old dystrophin-deficient mice (mdx mice). The number of contacts points between the SR/ER Ca2+ release channels (IP3R1), and the porine of the outer membrane of the mitochondria, VDAC1, measured using in situ proximity ligation assay, were greater in mdx cardiomyocytes. Expression levels of IP3R1 as well as the mitochondrial Ca2+ uniporter (MCU) and its regulated subunit, MICU1, were also increased in mdx heart. MICU2 expression was however unchanged. Furthermore, the mitochondrial Ca2+ uptake kinetics and the mitochondrial Ca2+ content were significantly increased. Meanwhile, the Ca2+-dependent pyruvate dehydrogenase phosphorylation was reduced, and its activity significantly increased. In Ca2+-free conditions, pyruvate-driven complex I respiration was decreased whereas in presence of Ca2+, complex I-mediated respiration was boosted. Further, impaired complex I-mediated respiration was independent of its intrinsic activity or expression which remain unchanged but is accompanied by an increase in mitochondrial reactive oxygen species production. Finally, mdx mice were treated with the complex I modulator metformin for one month. Metformin normalized the SR/ER-mitochondria interaction, decreased MICU1 expression and mitochondrial Ca2+ content and enhanced complex I-driven respiration. In summary, before any sign of dilated cardiomyopathy, the DMD heart displays an aberrant SR/ER-mitochondria coupling with an increase mitochondrial Ca2+ homeostasis and a complex I dysfunction. Such remodeling could be reversed by metformin providing a novel therapeutic perspective in DMD.